Perancangan Sistem Penilaian Kinerja Karyawan (SIPIKA) Berbasis Web Di Grand Mansion Hotel Menggunakan Metode Waterfall - Khoirul Anam (Teknologi Informasi : Teori, Konsep, dan Implementasi : Jurnal Ilmiah, 2026)
Employee performance assessment is an important aspect in determining the quality of performance. Grand Mansion as a company engaged in the hospitality service sector requires an effective and efficient system to carry out the performance assessment process. This study aims to design and build a website-based SIPIKA (Employee Performance Assessment System) using the Waterfall method as a system development approach. The Waterfall method was chosen because of its systematic and structured development stages, including needs analysis, system design, implementation, testing, and maintenance. The result of this study is a web-based application that simplifies the employee performance assessment process digitally, accurately, and can be accessed by management in real- time. With this system, Grand Mansion is expected to improve the quality of assessments, as well as support data-based decision making.